2014
DOI: 10.1530/erc-14-0389
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin receptor expression in hepatocellular carcinoma: prognostic and therapeutic considerations

Abstract: Sorafenib is the only systemic therapy to demonstrate a significant survival benefit over supportive care in robust randomised controlled trials for advanced hepatocellular carcinoma (HCC). In the context of an intense search for prognostic and predictive factors for response and efficacy of different systemic therapies (including sorafenib), a number of molecular targets have been identified, paving new avenues for potential therapeutic opportunities. Such molecular targets include somatostatin receptor (SSTR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…Several studies have evaluated the potential prognostic value of SSTR expression profiles in NET. 68,22 However, most have included a relatively small number of samples or examined a limited number of SSTR subtypes. Recently, one comparatively comprehensive study evaluated expression of SSTR1 to SSTR5, in 31 midgut and 55 pancreatic NETs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have evaluated the potential prognostic value of SSTR expression profiles in NET. 68,22 However, most have included a relatively small number of samples or examined a limited number of SSTR subtypes. Recently, one comparatively comprehensive study evaluated expression of SSTR1 to SSTR5, in 31 midgut and 55 pancreatic NETs.…”
Section: Discussionmentioning
confidence: 99%
“…5,9,10,21 Several prior studies have examined associations between expression of somatostatin receptors and prognosis, though most studies have focused primarily on SSTR2. 68,22 In a study evaluating 79 pancreatic NETs for expression of SSTR2, high expression of SSTR2 was associated with a favorable prognosis. 22 Other studies including a range of gastroenteropancreatic NET have similarly found that SSTR2 expression is associated with favorable outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Somatostatin and chemically designed analogues (SSAs), such as octreotide and lanreotide, have direct and indirect antitumour effects . These effects are mediated through G‐protein‐coupled somatostatin receptors (SSTR1–SSTR5).…”
Section: Introductionmentioning
confidence: 99%
“…9,[12][13][14][15][16][17][18][19] Somatostatin and chemically designed analogues (SSAs), such as octreotide and lanreotide, have direct and indirect antitumour effects. [20][21][22][23] These effects are mediated through G-protein-coupled somatostatin receptors (SSTR1-SSTR5). SSAs bind SSTR2 with high affinity, whereas they bind SSTR1, SSTR3 and SSTR5 with much lower affinity, and no binding has been demonstrated for SSTR4.…”
Section: Introductionmentioning
confidence: 99%
“…More interesting data came in to light with clinical studies of Somatostatin and its long acting analogues for advanced HCC with very promising initial results[11,12], given the antiproliferative activity of the hormone and the positivity of HCC in somatostatin receptors in roughly 40% of the tumors[13]. Further publications have documented that somatostatin leads to apoptosis and has antineoplastic properties.…”
Section: The Story Of Near-failed Systemic Treatmentsmentioning
confidence: 99%